Investigating Students’ Mathematical Problem-Solving Errors on Relations and Functions Through Newman’s Error Analysis - Barokah, Aulia; Arcat, Arcat; Nurrahmawati, Nurrahmawati (International Journal of Applied Learning and Research in Algebra, 2026)
Purpose – Students’ mathematical problem-solving ability remains low, particularly in the topic of relations and functions, as evidenced by frequent errors in solving problem-solving tasks. This study aims to identify and analyze the types of errors made by eighth-grade students in solving mathematical problem-solving questions on relations and functions using Newman’s Error Analysis. Methodology – This study employed a qualitative, descriptive research design. The participants were 29 Grade VIII.6 students from State Junior High School 1 Rambah. Data were collected through written problem-solving tests, semi-structured interviews, and documentation. The data were analyzed using Newman’s Error Analysis framework, which includes reading, comprehension, transformation, process skills, and encoding stages, following the steps of data reduction, data display, and conclusion drawing. Findings – The results indicated that the least frequent error was reading errors (36.2%), followed by comprehension errors (91.4%) and transformation errors (89.7%). The most frequent errors were process skills errors and encoding errors, each occurring in 100% of students’ responses. These findings suggest that students experience significant difficulties in executing mathematical procedures and expressing final answers correctly. Novelty – This study provides a detailed error profile of students’ problem-solving processes on relations and functions using Newman’s Error Analysis, highlighting critical stages where students consistently fail. Significance – The findings benefit mathematics teachers, curriculum developers, and researchers by providing insights into common student errors and supporting the development of instructional strategies that utilize students’ errors as learning resources to improve problem-solving ability.